Canto de intervenção em Portugal: "o povo é quem mais ordena” - Arruda, Ludmila Jones (2016)
Between 1933-1974, Estado Novo (New Estate), na authoritarian and opressive regime ocurred in Portugal under the government of António de Oliveira Salazar, brought huge impacts in Portugal, worsened by the beginning of the Colonial War in 1961. This situation led to a number of protests, gatherings, academic groups, ativists, literary productions and revolutionary songs which denounced the politics and revealed the fight, the dissatisfaction and the popular discontentment – being the core of this research. Inside Lusophone studies, the present paper aims to investigate the poetic and linguistic discursive elements present in Portuguese intervention songs composed before and after the Carnation Revolution (1974). The historic aspects of the Estado Novo is – mainly – based on the studies of Meneses (2011), Rosas (2013) and Pimentel (2007, 2011) specially on how the government used to act through censorship, which stopped the spread of protest songs and the diffusion of ideas which were against Salazar’s ideology. In order to select the songs for the analysis, six people were interviewed, amongst ativists and singers who imposed against the censorship: the singers are José Jorge Letria, Francisco Fanhais and Sérgio Godinho; along with academics Fernando Rosas, Pedro Calafate and António Borges Coelho – who contributed by giving important information and pointing songs which were significant in that period. In this aspect, in order to deal with memory, the theories of Halbwachs (2013), Le Goff (1996) and Traverso (2009) were relevant. The seven songs, Grândola Vila Morena, Menina dos Olhos Tristes, Vampiros, O Menino do Bairro Negro, sung by Zeca Afonso, Cantar da Emigração and Trova do Vento que Passa, by Adriano Correia de Oliveira, and finally Liberdade, by Sérgio Godinho - were also chosen considering the popularity the songs gained during the period, due to the action of the censorship. Based on Raposo (2000) and Letria (1999, 2013) to help the analysis, it was possible to outline elements which proved that those songs were important for the identity re(construction). Also, it is important to mention that such songs remain latent in the present, specially after the last European crisis when several of those songs were chanted again, covered by a new symbolic value, but rescueing the revolutionary characteristics present in their contents.